The Effectiveness of Career Information to Improve The Entrepreneurial Attitudes of Students (Jurnal Bimbingan Konseling, 2019)
This study aimed to determine the effectiveness of career information to improve the entrepreneurial attitudes of the students of Muhammadiyah Vocational High School Bulakamba (SMK Muhammadiyah Bulakamba). The experimental research method by using Post-test – Only Control Design was employed and involved as many as 30 students in the experimental class and 30 students in the control class as the research subjects. For more, the calculation results of t-test showed that the entrepreneurial attitude of the group which received career aspiration-based career information was higher than the group which got no career information on the students of SMK Muhammadiyah Bulakamba (tvalue= 3.847, p < 0.01). In conclusion, this study asserts the role of Guidance and Counselling in developing school entrepreneurship.